Types of forest and timber reserves of plain beech stands in Ukraine - Myklush Stepan; Myklush Yurii; Havryliuk Serhii; Savchyn Volodymyr (Наукові праці Лісівничої академії наук України, 2019)
Forest management on a typological basis foresees that forest site types and correct values of silvicultural indices of stands, including volumes of stands, reliably established during forest management activities allow planning appropriate forest management measures to increase the stands productivity and improve forest resource use. In accordance with the forest management instructions requirements, silvicultural indices are determined by the visual-measuring method with a certain accuracy standard. According to forest management data, plain beech stands and plantations with beech in the tree species composition are represented by inventory stands of various sizes in 74 forest site types, in particular in conditions of pine fairly infertile site types – 6, oak fairly fertile site types – 36 and oak fertile site types – 32 forest types that cover hygrotopes from dry to wet. Researchers of beech forests identify a smaller number of forest site types, usually from 25 to 35, in which the beech is represented as type-forming species. The biggest number of beech forest site types, namely 12 are allocated by for-est management in conditions of oak fairly fertile site types, six in fresh and six in moist hygrotopes. Under the same conditions, common beech, as the second main species, forms 13 site types of forest, mainly in humid hygrotopes, namely 7. In oak fairly fertile site types, common beech forms 11 forest site types and as the second main species forms 13 forest site types. Researchers of beech forests identify three times smaller amount of beech forest site types in oak fairly fertile site types, and in oak fertile site types only two forest site types were allocated. The given variety of forest site types established visually at the time of forest management of available tree species in stands does not correspond to the list of pos-sible forest types that are described in literature. Form factor is not correct (varying within 0.158-4.080) for the 36.7% of the to-tal number of inventory plots. According to the beech yield tables form factors are not less than 0.424 and do not exceed 0.840. In young stands, the differences in values of volumes compared to yield tables or standard tables can exceed 100%, while in mature and over mature stands the difference in stocks does not exceed 20% and rare-ly exceed 25-35%. For stands volumes determination with accuracy in accordance with the regula-tions, it is reasonable to accomplish the correctness of their determination using form factor, because for each species it has definite values depending on age and stand height. It is reasonable to develop the substantiated list of forest site types, evaluation of volume stock determination and actualization of sylviculture indexes for database of inventory for main tree species of Ukraine. It will be used as effective tool for the realization of permanent system for forest management planning.